Facies analysis and depositional model for the Oxfordian Hanifa Formation, Central Saudi Arabia. (December 2022) - Bashri, Mazin; Kaminski, Michael A.; Abdullatif, Osman; Humphrey, John; Makkawi, Mohammed; Swennen, Rudy; Ali, Omer; Adam, Ammar; Salih, Moaz; Babiker, Jarrah
Abstract: The Jurassic was a time for major global changes in climate, tectonics, and oceanography, reflected in the southern Neo-Tethys Ocean by a distinct transition from carbonate-poor to carbonate-dominated sedimentation. To better constrain the effect of this turning point in the Late Jurassic, key outcrops of Oxfordian deposits of the Arabian Plate were investigated through detailed sedimentologic analysis. High-resolution (centimeter-scale) description and analysis of eight outcropping sections with a cumulative thickness of 461 m through the Oxfordian Hanifa Formation along a N–S 535 km-long transect in central Saudi Arabia are used to develop a comprehensive conceptual depositional evolution through time. Nine sedimentary lithofacies are interpreted and grouped into four facies associations. These associations include: I) outer-ramp association (FA1), II) mid-ramp association (FA2), III) inner-ramp grainy-facies association (FA3), and VI) inner-ramp reefal association (FA4). The lithofacies succession distinguishes two depositional phases, a middle Oxfordian homoclinal ramp (Phase 1) that corresponds to the Hawtah Member, and a late Oxfordian reef-bearing carbonate ramp (Phase 2) that corresponds to the Ulayyah Member. After being restricted to the high latitudes in the northern Neo-Tethys during early and middle Oxfordian ages, the carbonate ramp evolution within the Hanifa Formation reflects the expansion of scleractinian coral reefs over the southern Neo-Tethys passive margin in the late Oxfordian. However, the distribution of the corals in the Arabian Plate is mainly controlled by water salinity and siliciclastic input; they are absent northward due to hypersalinity and southward due to siliciclastic input. Furthermore, the differential subsidence and the resulting uneven topography, in addition to the eustatic sea level variation during the Oxfordian age, controls the distribution of different depositional styles over the Arabian Plate (homoclinal ramp, distally-steepened ramp, rimed shelf, and intrashelf basin). Highlights: The Oxfordian eustacy and differential tectonism controlled the basin geometry and southern Neo-Tethys' depositional model. The findings of this study are useful for correlation to other Oxfordian successions of the southern Neo-Tethys. Middle Oxfordian homoclinal carbonate ramp has evolved to include distributed reef buildups in the late Oxfordian. Siliciclastic facies are described for the first time in the Oxfordian Hanifa Formation outcrops.